Pharmacotherapeutic considerations and options for the management of osteoarthritis in women. (23rd March 2020) - Trivedi, Sunny; Fang, William; Ayyalasomayajula, Ishan; Vangsness, C. Thomas
ABSTRACT: Introduction: Osteoarthritis is a chronic disease that leads to the destruction of articular cartilage and joints. As the most common joint disorder, osteoarthritis poses a great burden to the healthcare system. Most importantly, osteoarthritis is a heterogeneous disease characterized by a wide range of clinical features, phenotypes, and treatments. The burden of osteoarthritis is not equally distributed between men and women. Women have an increased risk of developing osteoarthritis, with worse symptoms, and poorer outcomes. Areas covered: In this paper, the authors discuss pathophysiological considerations such as the wide spectrum of OA phenotypes. Women share many OA phenotypes with men including genetics, age, and trauma. Specific phenotypes from metabolic, anatomical, and hormonal influences vary greatly between the two sexes. This paper discusses the various current pharmacological treatment options for osteoarthritis including NSAIDs, Acetaminophen, Opioids, Duloxetine, SYSADOAs, monoclonal antibodies, intra-articular injections and hormonal therapy. Expert opinion: Further investigations of the pathophysiology of osteoarthritis are necessary to improve treatment options specific to women. As our understanding of the complex biology of osteoarthritis and the information surrounding it improves, newer and more effective treatments may decrease the suffering of osteoarthritis in a more efficient and less costly way.